Experimental investigation on concrete beams reinforced with basalt fiber reinforced polymer bars. (2021) - Elango, K.S.; Gopi, R.; Jayaguru, C.; Vivek, D.; Saravanakumar, R.; Rajeshkumar, V.
Abstract: This paper dealt with the flexural behaviour study on reinforced concrete beams with conventional steel and basalt rebar using Portland Pozzolana Cement. Conventional steel bars are vulnerable to various environmental attacks and aggressive attacks such as corrosion. Basalt rebar can effectively overcome this problem due to the enhanced properties like inhibiting corrosion, high tensile strength, low young's modulus, lightweight and resist electrical conductivity. In this paper, flexural behaviour of conventional Steel Reinforced Beam (SRB) and Basalt Fiber Reinforced Polymer beam (BFRB) were investigated experimentally and test results arrived were elaborately discussed. It has been noticed that BRB shows significant greater deflection when compared to SRB due to lower elastic modulus, whereas flexural load carrying capacity of BRB increases due to enriched tensile strength property in basalt rebar, significant increase of tensile strength in BRB. The results revealed that basalt rebar can be effectively used in construction as a replacement of conventional steel reinforcement for sustainable development.